Choose a value for x, say, x=1. Then for that x, you have y=3 times 1, then minus 3, which is 0. Put a dot on the graph at the place which is lined up with x=1 and y=0. Choose another x, and work out what is y and put another dot. Do it for more values. Finally draw a line which is smooth (no kinks) that join up the dots. In this case it should turn out to be a straight line.
y-3x-3 y=3x+3 A line with a slope of 3 crossing the y-axis at 3.
3x + y = -1 y = -3x - 1 The graph is a straight line, with a slope of -3, passing through the point Y = -1 on the y-axis.
-7
y = 3x =3(6) = 18 ... the ordered pair is (x,y) = (6,18)
3x + y = 7 First, turn the equation into the slope-intercept form, y = mx + b, where m is the slope of the graph that that equation represents (solve for y).3x + y = 7 subtract 3x to both sidesy = -3x + 7So you clearly see that the slope is -3.
The graph of [ y = -3x ] is a straight line, through the origin, with slope of -3 .
1
y-3x-3 y=3x+3 A line with a slope of 3 crossing the y-axis at 3.
3x - 9y = 27-9y = -3x + 279y = 3x - 27y = x/3 - 3The graph is a straight line, with (slope = 3), and passing through the point (y = - 3) on the y-axis.
3x + y = -1 y = -3x - 1 The graph is a straight line, with a slope of -3, passing through the point Y = -1 on the y-axis.
First of all, if 'x' is 3, then 'x' doesn't equal -3x+3 . You must mean y = -3x + 3.If x=3, then (-3x + 3) = -6 .The graph is the point (3, -6) .
-7
Put in this form.......Y = mX + bb = Y intercept.3X - 2Y = 6- 2Y = - 3X + 6Y = (3/2)X - 3================
y = 3x =3(6) = 18 ... the ordered pair is (x,y) = (6,18)
y-3x-3 y=3x+3 A line with a slope of 3 crossing the y-axis at 3.
3x + y = 7 First, turn the equation into the slope-intercept form, y = mx + b, where m is the slope of the graph that that equation represents (solve for y).3x + y = 7 subtract 3x to both sidesy = -3x + 7So you clearly see that the slope is -3.
Get in function form. - 3X - Y = 4 - 1(- Y = 3X + 4) Y = - 3X - 4 ----------------------------solve for X and Y by the 0 out method - 3X - 4 = 0 - 3X = 4 X = - 4/3 --------------- Y = - 3(0) - 4 Y = - 4 -------------- Draw a line linking those points.